Effect of fatigue on biomechanical variable changes in overhead badminton jump smash - Rusdiana, A.; Subarjah, H.; Imanudin, I.; Kusdinar, Y.; Syahid, A. M.; Kurniawan, T. (Annals of Applied Sport Science, 2021)
Background. The badminton forehand overhead jump smash is one of the high speed and powerful motions among various racket sports. Objectives. The purpose of this study is to analyze the effect of fatigue on the kinematic variable movement changes during overhead jump smash in badminton. Methods. This study is descriptive quantitative research with the pre-test and post-test design methods used to obtain data from 15 male badminton players, aged 19.4 ± 1.6 years, height 1.73 ± 0.12 m, and weight 60.8 ± 3.7 kg. The study used three high-resolution handy-cams, motion software Frame DIAZ IV, and 14 point manual markers to analyze body segments` movement when carrying out a jump smash. Furthermore, an ergo treadmill was used to test the players` level by running. Results. The results showed that the shuttlecock velocity was faster during pre-fatigue (188 km/h) than under the condition (145 km/h). A significant difference showed in the angle of shoulder internal rotation (p=0.048) and wrist palmar flexion (p=0.037) at the instant of maximal shoulder external rotation phase. Furthermore, there were significant differences in the shoulder`s internal angular velocity (p=0.042), elbow extension (p=0.035), forearm supination (p=0.024), and wrist Dorsi dorsiflexion.040). Conclusion. In conclusion, fatigue reduces players` performances during jumping smash in badminton, thereby leading to slower shuttlecock speed and changes in body segment movements.